2020
DOI: 10.1097/jcp.0000000000001201
|View full text |Cite
|
Sign up to set email alerts
|

Re-Kinect

Abstract: Any pre-existing medical condition, n (%) 0.0886 0.1799 Yes 436 (81.5%) 177 (86.8%) No 99 (18.5%) 27 (13.2%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…TD has been associated with decreased quality of life, increased hospitalizations, speech and eating difficulties, cognitive dysfunction, decreased employment, social withdrawal, stigmatization, amplified emotional distress, and increased psychopathology in the underlying psychiatric disorder when patients with TD are compared with non-TD counterparts. 2,11,12,[29][30][31] Although causality has not been established, and TD may be a marker of more severe illness for some patients, these potential negative effects underscore the importance of assessing TD and its impact.…”
Section: Importance Of Assessing the Impact Of Tdmentioning
confidence: 99%
See 2 more Smart Citations
“…TD has been associated with decreased quality of life, increased hospitalizations, speech and eating difficulties, cognitive dysfunction, decreased employment, social withdrawal, stigmatization, amplified emotional distress, and increased psychopathology in the underlying psychiatric disorder when patients with TD are compared with non-TD counterparts. 2,11,12,[29][30][31] Although causality has not been established, and TD may be a marker of more severe illness for some patients, these potential negative effects underscore the importance of assessing TD and its impact.…”
Section: Importance Of Assessing the Impact Of Tdmentioning
confidence: 99%
“…More than half of patients with TD reported that their employment status was "disabled" (P = 0.0027 vs patients without TD). 2 Stigma associated with TD can also lead to a perception that individuals with orofacial symptoms are less employable than individuals without TD. 33,34 Negative effects on employment may also be a result of patients with uncontrolled TD avoiding public places and attempting to hide their abnormal movements.…”
Section: Social Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute number of people at risk of TD may be growing due to expanding indications and off-label prescribing of antipsychotics [ 8 - 11 ]. While recent studies confirm the impact of TD on quality of life that was often overlooked in the past [ 12 , 13 ], effective treatment of TD using vesicular monoamine transporter-2 inhibitors (VMAT2s) is now available [ 14 , 15 ]. Finally, research into the pharmacology underlying TD may shed light on basal ganglia organization and function.…”
Section: Introductionmentioning
confidence: 99%
“…2020 m. at lik ta me ty ri me pa skelb ta, kad ið 204 pa cien tø, ser gan èiø VD, 75,5 % tei gë esan tys su si drovë jae ar su si gë dae dël sa vo ne va lin gø ju de siø, ku riø ne ga lë jo su val dy ti. To kie jaus mai ga li su stip rin ti jau esa mus psichiat ri nius simp to mus (pvz., pri slëg tà nuo tai kà, ne ri mà) ir pri si dë ti prie stig ma ti za ci jos bei so cia li nës izo lia ci jos [8]. Pas ta rai siais me tais ávy ko ne pa pras tai di de lis po stû mis nuo ni hi lis ti nio po þiû rio á VD, kai li te ra tû ro je pa si ro dë daug pub li ka ci jø, ku rio se ap ta ria mos nau jos áþval gos apie VD pa to fi zio lo gi jà ir nau jus vais tus [9].…”
unclassified